The severity of pandemic H1N1 influenza in the United States, April - July 2009 - Presanis, A; De Angelis, D; Hagy, A; Reed, C; Riley, S; Cooper, B; Finelli, L; Biedrzycki, P; Lipsitch, M (Public Library of Science, 2009)
Background: Accurate measures of the severity of pandemic (H1N1) 2009 influenza (pH1N1) are needed to assess the likely impact of an anticipated resurgence in the autumn in the Northern Hemisphere. Severity has been difficult to measure because jurisdictions with large numbers of deaths and other severe outcomes have had too many cases to assess the total number with confidence. Also, detection of severe cases may be more likely, resulting in overestimation of the severity of an average case. We sought to estimate the probabilities that symptomatic infection would lead to hospitalization, ICU admission, and death by combining data from multiple sources.